A Typological Classification of Cyrillic Manuscripts Containing Texts from Piotr Skarga’s Book Żywoty Świętych - Sapozhnikova, Galina (Slavistica Vilnensis, 2020)
The article is devoted to the typological classification of manuscripts containing Ruthenian and Church Slavonic translations of the extensive Polish book Żywoty świętych written by the Jesuit Piotr Skarga. Unlike the Polish original, these translations have not been studied extensively and represent a specific part of Cyrillic writing of the Grand Duchy of Lithuania and the Kingdom of Poland. The objectives of the article are to show (1) what types of manuscripts did the translated texts from the book of the lives of Piotr Skarga fall into and to answer (2) which manuscripts contain a higher concentration of the translations. The data from special works on this topic were taken into account; the list of sources known from these works was significantly expanded. Most of the manuscripts were examined de visu. A description of the content has been prepared for each manuscript, the identified translations are included in the compiled consolidated catalog of such translations, and the results obtained were verified by comparing them with the lists of translated texts available in the studies. Both the internal structure and the content of the manuscripts in question made it possible to distinguish six typological groups, namely, miscellanies of the lives from Żywoty Świętych, miscellanies with mixed content, miscellanies of the Menaion type, the Festal Homiliary (Torzhestvennik), Didactic Gospels, and Synaxarion (Prologue). Apart from the unique miscellany containing nothing more than Cyrillic versions of hagiographical texts from Skarga’s Żywoty Świętych, the greatest concentration of these translations is attested in the Menaion type of miscellanies, which are structurally quite close to their printed Polish source.